Potassium intercalated multiwalled carbon nanotubes. (August 2016) - Chacón-Torres, J.C.; Dzsaber, S.; Vega-Diaz, S.M.; Akbarzadeh, J.; Peterlik, H.; Kotakoski, J.; Argentero, G.; Meyer, J.C.; Pichler, T.; Simon, F.; Terrones, M.; Reich, S.
Abstract: Full intralayer potassium intercalation in multiwalled carbon nanotubes MWCNTs was achieved by carefully engineering the nanotube morphology (length, width, and number of layers). The complete intercalation induced a high doping resulting in metallic nanotubes with a bright golden color. The successful intercalation of MWCNTs serves as a first step for obtaining controlled graphene nano-ribbons through exfoliation and potentially preparing superconducting nanotubes.